Implementasi Pembelajaran Berbasis Literasi dalam Menumbuhkan Minat Baca Peserta di SD Negeri 4 Pecangaan - Siti Yulia Zusnita; Lailatul Badriyah (Tunas Nusantara, 2022)
Reading is one of the inseparable foundations of literacy activities that children have. This study aims to describe the implementation of literacy-based learning at SD Negeri 4 Pecangaan and review the efforts made by the school and teachers in fostering the reading interest of students. This research method is descriptive qualitative with a type of case study. The subjects of the study were students of grade 6 of SD Negeri 4 Pecangaan. Data collection techniques were carried out by means of observation, interviews, and documentation. The results of this study show that SD Negeri 4 Pecangaan has implemented literacy-based learning that is shown by the school's efforts in providing infrastructure that supports students' reading interests such as reading corner rooms in each class, library rooms, as well as the application of literacy-based learning models conducted by teachers as an innovation step in fostering students' reading interests Implementation of literacy-based learning models includes introductory, smelting, intra-integration, extra-integration, storage, reminder and communication activities.